2020
DOI: 10.1002/rob.21992
|View full text |Cite
|
Sign up to set email alerts
|

A novel loop closure detection method with the combination of points and lines based on information entropy

Abstract: Visual simultaneous localization and mapping (visual-SLAM) is a prominent technology for autonomous navigation of mobile robots. As a significant requirement for visual-SLAM, loop closure detection (LCD) involves recognizing a revisited place,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…We have observed that this can be the result of wrong line detections between consecutive frames, which are due to the bad quality of the images and the corresponding perceptual aliasing that occurs among those lines, leading to a subsequent decrease in the pipeline performance. Notice that our proposal also outperforms (Gomez-Ojeda et al 2019;Han et al 2021), which are the solutions most similar to LiPo-LCD ++ , given that they are the only ones that combine points and lines for loop closure detection.…”
Section: Comparison With Other Solutionsmentioning
confidence: 89%
See 2 more Smart Citations
“…We have observed that this can be the result of wrong line detections between consecutive frames, which are due to the bad quality of the images and the corresponding perceptual aliasing that occurs among those lines, leading to a subsequent decrease in the pipeline performance. Notice that our proposal also outperforms (Gomez-Ojeda et al 2019;Han et al 2021), which are the solutions most similar to LiPo-LCD ++ , given that they are the only ones that combine points and lines for loop closure detection.…”
Section: Comparison With Other Solutionsmentioning
confidence: 89%
“…Some SLAM approaches (Pumarola et al 2017;Zhang et al 2019) have benefited from the combination of points and lines for image description. However, during the LCD stage, they only rely on point features, discarding line information that can be useful for some environments, unlike our approach (Company-Corcoles et al 2020), and others that adopt a dual scheme for LCD (Gomez-Ojeda et al 2019;Zuo et al 2017;Han et al 2021). Our approach resembles the idea of combining lines and points described in these works, though it differs in multiple aspects, such as (1) the point features that are employed, (2) how the visual vocabularies are built, (3) how image scores are calculated from the visual vocabularies and later combined, and (4) the spatial verification process.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Bampis et al (2016Bampis et al ( , 2018 combined the visual words' occurrences of sequence segments, that is, groups-of-images, to assist the matching process. Recently, points and lines were combined based on information entropy to realize accurate loop closure detection (Han et al, 2021).…”
Section: Approaches Using Hand-crafted Featuresmentioning
confidence: 99%
“…However, the noisy sensor measurements, modeling inaccuracies, and errors due to field abnormalities affect the performance of SLAM. Identifying known locations in the traversed route based on camera information to rectify the incremental pose drift is widely known as visual loop closure detection (Botterill et al, 2011;Han et al, 2021;Mei et al, 2010;Tsintotas, Bampis, & Gasteratos, 2018;Zhang, 2011). This operation is highly related to image retrieval, as the system tries to find the most similar visual entry within a visual database, which is explicitly built using camera measurements gathered along a trajectory.…”
Section: Introductionmentioning
confidence: 99%